Comparative Evaluation of Antioxidant Properties and Isoflavones of Tempeh Fermented in Two Different Wrapping Materials - Hashim, Normah; Tai, Chia Woon; Wen, Hui Xin; Ismail, Amin Razak; Kong, Kin Weng (Enviro Research Publishers, 2018)
Tempeh is an Indonesian traditional fermented soybean food that is well known for its nutritional value and health benefit. This study aimed to evaluate the effects of two commonly used packaging materials in tempeh production, namely banana leaf and polyethylene bag, on the antioxidant properties. Isoflavones, include daidzein and genistein, of tempeh fermented in banana leaf (TBL) and polyethylene bag (TP) were analysed with high-performance liquid chromatography. Total phenolic content and antioxidant activities were evaluated using Folin-Ciocalteu reagent, DPPH radical scavenging and β-carotene-linoleate bleaching assays, respectively. The changes of antioxidant properties of tempeh after different fermentation periods in both wrapping materials were observed, on day 0 (unfermented), day 1, day 2 and day 4. Total phenolic content, daidzein, genistein and the antioxidant activities were significantly (p < 0.05) increased in both TBL and TP as the fermentation progressed. A higher total phenolic content was found in TBL on day 1 and day 2 but TP exhibited the highest total phenolic content on day 4. Daidzein was the highest in TBL on day 2 but it was reduced on day 4 while genistein was the highest in TP on day 4. Antioxidant activities were positively (r = 0.272–0.969, p < 0.05) correlated to total phenolic content, daidzein and genistein. Although tempeh wrapped in banana leaf is a traditional way for tempeh packaging, it provided better antioxidant properties on day 1 and day 2, which is within the best period of tempeh consumption. Hence, the current findings provided useful information to manufacturer and consumer in selecting the suitable wrapping material for tempeh with optimal phytonutrients.